Pandangan Teori Belajar Sosial Kognitif Albert Bandura - Kanaya Yose Putri; Neviyarni; Herman Nirwana (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This research is a literature study research which aims to gain an understanding regarding social cognitive learning theory from various sources, research articles and several books. This research uses Moreno's book (2010) as the main data source and several other books and articles as complementary sources. The research results show that social cognitive learning theory is a theory developed by Albert Bandura, an American psychologist. Social cognitive learning theory emphasizes that learning can occur through a process of observation or what is known as observational learning. In this process, individuals learn by observing the behavior of others, understanding the consequences, and then imitating that behavior. Albert Bandura also emphasized modeling and the term triadic reciprocity to describe the interconnected interactions between an individual's environment, their personal beliefs, and the behavior they exhibit. The triadic concept of reciprocity proposed by Bandura can be implemented as an approach to classroom learning.